Diversity of Antibiotic Biosynthesis Gene-possessing Rhizospheric Fluorescent Pseudomonads in Japan and Their Biocontrol Efficacy - Someya, Nobutaka (Microbes Environ, 2020)
More than 3,000 isolates of fluorescent pseudomonads have been collected from plant roots in Japan and screened for the presence of antibiotic-synthesizing genes. In total, 927 hydrogen cyanide (HCN)-, 47 2,4-diacetylphloroglucinol (PHL)-, 6 pyoluteorin (PLT)-, 14 pyrrolnitrin (PRN)-, and 8 phenazine (PHZ)-producing isolates have been detected. A cluster analysis (≥99% identity) identified 10 operational taxonomic units (OTUs) in antibiotic biosynthesis gene-possessing pseudomonads. OTU HLR (PHL, PLT, and PRN) contained four antibiotics: HCN, PHL, PLT, and PRN, while OTU RZ (PRN and PHZ) contained three: HCN, PRN, and PHZ. OTU H1, H2, H3, H4, H5, H6, and H7 (PHL1-7) contained two antibiotics: HCN and PHL, while OTU H8 (PHL8) contained one: PHL. Isolates belonging to OTU HLR and RZ suppressed damping-off disease in cabbage seedlings caused by Rhizoctonia solani. Effective strains belonging to OTU HLR and RZ were related to Pseudomonas protegens and Pseudomonas chlororaphis, respectively. Antibiotic biosynthesis gene-possessing fluorescent pseudomonads are distributed among different geographical sites in Japan and plant species.